Planes of isotropic Poisson's ratio in anisotropic crystalline solids. (15th May 2020) - Shrikanth, S.; Knowles, Kevin M.; Neelakantan, Suresh; Prasad, Rajesh
Highlights: A formalism to calculate loading directions with isotropic Poisson's ratio in the transverse plane in all crystalline media. Isotropic loading directions need not lie along the symmetry axes of crystals. A surface to represent the anisotropy of Poisson's ratio for each loading direction. Abstract: It is shown that loading directions can exist in all single crystals for which Poisson's ratio is isotropic in the plane transverse to the loading direction. The body diagonals and the cube axes of cubic crystals, the four-fold axis in tetragonal crystals and the six-fold axis in hexagonal crystals are examples of such loading directions. However, these loading directions do not necessarily just lie only along high rotational symmetry axes. A new three-dimensional "anisotropy surface" is introduced to represent the degree of anisotropy of the Poisson's ratio within the plane normal to a loading direction for a particular choice of single crystal. Graphical abstract: Image, graphical abstract